The Influence of Types of Bacteria and Types of Compost Materials on Composting Results - Dian Rachma Agustin; Suprapti, Endang; Wiyono (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2025)
Composting is a biological process in organic materials that are broken down by microorganisms into stable organic fertilizers and are useful as organic fertilizers or compost, microorganisms have the ability to produce enzymes needed to process organic waste into compost that can be reused as fertilizer. The purpose of this study was to determine the influence of cellulolytic bacteria, rhizomonas, subtilis and cow rumen using waste materials from rice straw and corn plant waste in the composting process.This research was conducted in Bowan Village, Delanggu District, Klaten Regency with an altitude of Â± 130 meters above sea level in February to April 2024 and using a Completely Randomized Design (CRD) with 2 factors, namely: The first factor is a combination of bacteria consisting of 5 levels: D?: without bacteria, D1: cellulolytic, rhizomonas and cow rumen, D2: cellulolytic and subtilis, D3: rhizomonas and cow rumen, D4: cow rumen, The second factor is the type of compost material consisting of 2 levels: P1: Rice straw and P2: Corn plants. The parameters observed were compost odor, compost color, compost temperature, compost pH, composting time, water hold capacity, final compost weight and final compost water content. The results of the study showed that the provision of cellulolytic bacteria, subtilis, rhizomonas and cow rumen significantly affected the temperature and pH of the compost but did not significantly affect the composting time, water hold capacity, final weight of the compost and final water content of the compost. The use of rice straw waste and corn waste had a very significant effect on pH and significantly affected the composting time, final weight of the compost and final water content of the compost but did not significantly affect the temperature and water hold capacity.